(3MGTjI Ydi GdMGTjI GdTQjaI dTQM JfhjQ GdeWGdYs - (3ZjGK GdOjf efUhQ GdTjQGRis; (3GdSjO GdTQja GdMSfj , YHO GdcQje GdMSfj, GdSjO GdTQjas
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ GdMbjQ ZjGK GdeTghQ s
(3BNQgG (B:s
(3hEfg jLhR Cf jchf deSCdI hGMOI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(1/369) s
Keywords: (3GdadSaI hGdefWbs